Express Release Validation: Enhancing Quality in tight development timelines - Moreira, José Ricardo B.; Santana, Maria Deolinda de O.; Silva, Gleiça Gabriela J.; Rocha, Raimundo F.; Bezerra, Erick Costa (Anais do Simpósio Brasileiro de Engenharia de Software (SBES), 2025)
The industry’s strong demand for increasingly faster software releases has led testing professionals to seek agility in their processes. This article proposes the Express Release Validation approach, based on essential quality criteria and the experience of quality assurance analysts in the project. This new strategy seeks to optimize testing time by focusing on the most critical aspects of the system without compromising the product reliability.